Control de inventarios de logística inversa en los centros de distribución de alimentos perecibles - Cepeda Núñez, Manuel Eduardo (2021)
This research consists of an Inventory Design for Reverse Logistics in Perishable Food Distribution Centers, in order to create an updated procedure for the control of the product that is generated from customer returns, the correct handling of inventories and their final destination. The first chapter highlights the importance of the thesis topic and the contribution to perishable food companies and the environment.........